Pendampingan dan Pembuatan Pupuk Organik dalam Mengurangi Biaya Pupuk Petani Desa Rowo Gempol - Mohammad Zidan Rafsanjani; Siti Fatimatuzzahro; Wafiq Nur Azizah; Samsul Arifin; Utami Puji Lestari; Mila Hariani; Arif Rachman Putra (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
Organic fertilizers contain organic materials such as compost, manure, or other organic waste materials. When organic fertilizers are applied to the soil, they provide an abundant source of nutrients, including nitrogen, phosphorus, and potassium, as well as essential micronutrients. The community service activity program aims to empower farmers with the knowledge and skills to make organic fertilizers from local materials, which not only lower production costs but also improve soil quality and crop yields. The community service activity with the theme "Assistance and Making Organic Fertilizers in Reducing Fertilizer Costs for Farmers in Rowo Gempol Village, Lekok District, Pasuruan Regency" Through the Participatory Action Research method which includes preparation, processing, application, and evaluation, this program has succeeded in improving soil quality and supporting plant growth in the campus green area. Organic fertilizers, produced from campus organic waste such as dry leaves and food scraps, increase soil nutrient content and plant health, and reduce the negative impacts of synthetic chemicals. This activity also involves students in the process of processing and applying fertilizers, providing practical experience and raising awareness of the importance of sustainable agriculture and environmental management. The evaluation results showed a significant positive impact on soil quality and plant growth, with more fertile soil and healthier plants. In addition to the ecological benefits, the program plays an important educational role, by increasing students' understanding of environmentally friendly practices and organic farming skills. The success of this model is expected to be replicated in other villages. so that the benefits of this program can be felt more widely and support the creation of more sustainable agriculture.